A voice of their own: women moving into their fifties. - Arnold E (Health Care for Women International, 2005)
This purpose of this qualitative study was to illuminate the developmental journey experienced by women moving into their fifties. A purposive sample of 23 women was asked to document any changes they perceived in themselves as they moved from their forties into their fifties. Themes identified included stepping out of the mold, letting go, walking in balance, moving in new directions, redefining relationships, and experiencing a freedom 'to be.' Understanding the patterns of meaning experienced by healthy women at midlife can provide clinicians with a blueprint for enabling women to become all they can be during late midlife and thereafter.